The Effect of Gamma Irradiation on the Growth and Multiplication of the In Vitro Shoot of Patchouli (Pogostemon cablin Benth.) - Banyo, Yunia Efrice Banyo Efrice; Indriyani, Serafinah; Widoretno, Wahyu (The Journal of Experimental Life Science, 2020)
The objective of this research was to evaluate the effect of gamma irradiation on shoot growth and multiplication of Patchouli (Pogostemon cablin Benth.) Two weeks-old in vitro shoots were irradiated gamma-ray, at doses of 0, 15, 30, 45, 60, and 75 Gy. The control shoot was not irradiated. The irradiated shoots were cultured on Murashige and Skoog (MS) medium supplemented with 0.1 mg.L-1 NAA and 0.3 mg.L-1 BA and incubated in a growth room for eight weeks at a temperature of 25±2°C. The results showed that the gamma irradiation inhibited the growth and multiplication of shoots. Explants irradiated with high-dose gamma-ray (45-75 Gy) had not formed shoot in four weeks of culture, while 58.3-83.3% of the explants without irradiation or irradiated at low doses 15 and 30 Gy formed shoots. The higher irradiation doses increased percentage of browning explants and reduced the percentage of forming shoots. Within the eight weeks of culture, explant without irradiation was able to form shoots at the percentage of 100% with 24 shoots per explant, while explants irradiated at 15-45 Gy were able to grow form shoots at the percentage of 77.7-95.5%. The high doses-irradiated explants (60 and 75 Gy) were only able to form shoots less than 13-20%, with 2-3 shoots per explant. Keywords: Gamma rays (Gy), in vitro shoot, Pogostemon cablin Benth.